PENGARUH PEMBERIAN JUS BIT TERFORTIFIKASI FESO4 INSTAN (JUS BEEFE) DALAM MENANGGULANGI ANEMIA ATLET REMAJA PUTRI - Mirza Hapsari Sakti Titis Penggalih; Ibtidau Niamilah; Yuga Putri Pramesti; Nia Bactiar; Sheila Kusuma Wardhani (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2021)
Prolonged physical exercise has the risk of increasing free radicals which will affect the breakdown of red blood cells and promote the risk of decreased hemoglobin. Adolescent female athletes have a risk of decreasing hemoglobin due to menstruation. This situation can get worse if the athletes have iron defi-ciency or anemia as the result of poor diet choice. Increased radicals and anemia affect the amount of oxygen carried to the tissues and the maximum volume of oxygen an individual can use to produce energy (VO2 max). Beets have benefits for athlete's performance and have been developed into an instant drink. The purpose of this study was to determine the effect of an instant FeSO4 fortified beet juice (BeeFe juice) in overcoming anemia on female adolescent athletes. This research using an experimental study with controlled trial pre-posttest design. Twenty-nine adolescent female athletes, aged 13-19 years, were divided into two groups. Fe tablet supplementation (containing Fe 60 mg) was given to 15 athletes in the control group and BeeFe juice (containing Fe 17 mg) was given to 14 athletes in the treatment group du-ring the luteal and menstruation phase (±14 days). Hemoglobin levels, Malondialdehyde (MDA) and maxi-mal oxygen volume (VO2 max) were examined before and after the intervention. Data were analyzed using paired t-test and independent t-test IBM SPSS version 22. This research has obtained Ethical Appro-val with number KE/FK/0633/EC/2018 from the Ethical Commission of FKKMK UGM. The results showed no significant difference between the group given Fe tablets and the group given BeeFe juice on hemo-globin levels (P>0.05), MDA levels (P>0.05), and VO2 max levels (P>0.05) in the menstrual and luteal phases of menstruation. It can be concluded that BeeFe juice has the same effectiveness as commercial Fe tablets. BeeFe juice can be an alternative food ingredient in iron supplementation.